Perception of rigidity in three- and four-dimensional spaces - He, Dongcheng; Nguyen, Dat-Thanh; Ogmen, Haluk; Nishina, Shigeaki; Yazdanbakhsh, Arash (Frontiers in Psychology, 2023)
Our brain employs mechanisms to adapt to changing visual conditions. In addition to natural changes in our physiology and those in the environment, our brain is also capable of adapting to “unnatural” changes, such as inverted visual-inputs generated by inverting prisms. In this study, we examined the brain’s capability to adapt to hyperspaces. We generated four spatial-dimensional stimuli in virtual reality and tested the ability to distinguish between rigid and non-rigid motion. We found that observers are able to differentiate rigid and non-rigid motion of hypercubes (4D) with a performance comparable to that obtained using cubes (3D). Moreover, observers’ performance improved when they were provided with more immersive 3D experience but remained robust against increasing shape variations. At this juncture, we characterize our findings as “3 1/2 D perception” since, while we show the ability to extract and use 4D information, we do not have yet evidence of a complete phenomenal 4D experience.